Enable high reversibility of Fe/Cu based fluoride conversion batteries via interfacial gas release and detergency of garnet electrolytes. (December 2022) - Liu, Yangyang; Lei, Meng; Lai, Chuanzhong; Meng, Junwei; Wu, Xiaoxue; Yu, Yifan; Zhang, Yang; Li, Chilin
Graphical abstract: Abstract: Garnet-type Ta-doped Li7 La3 Zr2 O12 (LLZTO) electrolyte suffers from unstable chemical passivation under air exposure, responsible for the poor interfacial wettability and conductivity with Li metal. Instead of conventional methods to remove surface contaminants by mechanical polishing, acid etching and high temperature reduction, herein we propose a simple strategy of interfacial gas release and detergency to smartly convert Li2 CO3 passivation layer into ion-conductive Li3 PO4 domains at mild temperature (∼200 ℃). The in-situ formation of PH3 vapor and its phosphorization enables a dramatic decrease of Li/garnet interfacial resistance down to 2 Ω cm 2 at room temperature (RT). The improved interfacial wettability and conductivity endow the symmetric cells with ultra-stable galvanostatic cycling over 1500 h and high critical current density of 2.6 mA/cm 2 . The high coulombic efficiency of Li plating enables a high reversibility of solid-state NCM811/Li cells even under a low N/P ratio (∼4) and high cut-off voltage of 4.5 V at RT. The prototype of fluoride-garnet solid-state batteries are successfully driven as rechargeable system (rather than widely known primary battery) with high conversion capacity (400 ∼ 500 mAh/g) and high-rate performance (251.2 mAh/g at 3 C). This interface infiltration-detergency approach provides a practical solution to the achievement of high-energy solid-state Li metal batteries.